Cosmic Aesthetics - Braude, Stephen (Journal of Scientific Exploration, 2020)
In my book Immortal Remains (Braude, 2003), I considered an intriguing argument William James offered against the suggestion that mediumistic evidence for postmortem survival could be explained away in normal, or at least non-survivalist, terms—that is, either by appealing to what I’ve called The Usual Suspects (e.g., misperception, hidden memories, fraud) or The Unusual Suspects (e.g., dissociation + latent abilities, exceptional memory, or living-agent psi). More specifically, James was concerned with a fascinating, but frustrating, feature of the material gathered from mental mediumship—namely, that even the best cases present a maddening mixture of (a) material suggesting survival, (b) material suggesting psi among the living, and (c) apparent rubbish. At their best, of course, mediums furnish detailed information for which no normal explanation will suffice. In the cases most strongly suggesting survival, that information concerns the past lives of the deceased. But sometimes mediums also provide information on the present actions, thoughts, and feelings of the living, and that’s one reason why some cases suggest psi among the living, and why a living-agent–psi interpretation of mediumship is difficult to rule out. After all, information about present states of affairs is not something to which the deceased would enjoy privileged access. Moreover, to complicate matters further, . . . gems of correct, detailed, and relevant information are nearly always imbedded in an immense matrix of twaddle, vagueness, irrelevance, ignorance, pretension, positive error, and occasional prevarication. (Broad, 1962, p. 259)